Menelisik Problematika Desa Mandiri Budaya - Andriana Wulandari; Supardal Supardal (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to explore the dilemma of Governability in the implementation of the Cultural Independent Village policy at the village/sub-district level. These dilemmas include coordination between local governments and local stakeholders, as well as obstacles related to the allocation and use of Mandiri Budaya Village funds. This study uses a qualitative descriptive method consisting of observation, documentation, and interviews as an approach to collect data. Observations were made to observe the practice of implementing the Cultural Independent Village policy in the field, while documentation was used to analyze documents related to the policy. In addition, interviews were conducted with various related parties, including local governments, local stakeholders, and the community, to gain a comprehensive understanding of the existing problems. The results of the study show that the implementation of the Cultural Independent Village policy is faced with various obstacles and dilemmas. Although there has been progress in several aspects, such as priorities on the four points in the Cultural Independent Village, there is still a gap between the policy concept and field practice. The lack of awareness of local culture among the community, the lack of coordination between stakeholders, and problems related to the allocation and use of funds are the main challenges that need to be overcome.